Formation of Imidazolones by Ring Closure of α-Isocyanoamides: Exploring New Reactivities - Frippiat, Steven; Leterrier, Claire; Baudequin, Christine; Hoarau, Christophe; Bischoff, Laurent (Synlett, 2020)
Base-mediated ring closure of α,α-disubstituted α-isocyanoamides with further electrophilic trapping has previously been explored, but with limited applications. In this work, we wished to unravel the reactivities of these compounds and, in particular, to allow palladium-catalyzed coupling at the C2 position.
Keywords: isocyanides; imidazolones; lithium compounds; palladium catalysis; coupling